(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article examines the key trends in the development of the pharmaceutical industry in the Republic of Uzbekistan, considering the influence of globalization, competitive dynamics, state regulation, and technological advancements. The study highlights the rapid transformation of the global pharmaceutical market and the increasing role of innovation in ensuring the industry’s sustainable growth. Special attention is given to the localization processes within the pharmaceutical sector, emphasizing the government’s role in promoting domestic production. The paper analyzes the factors affecting pharmaceutical enterprises, including research and development (R&D) expenditures, market risks, and the challenges of high-tech drug production.